Business Backup Technology Research on Service Access and Control Layer of IP Metropolitan Area Network - Jin Huang; Yao Xue (Dianxin kexue)
As more and more telecom services carrying over the IP network, the IP MAN needs higher reliability requirements. The service access control layer is the key equipment of converging multi-service in IP MAN, and plays a connecting function in the network. Based on the operational practice and operational testing, the current state of technology of the service access control layer equigment business back up was analyzed. The methods and recommendations with building high reliability service access control layer in the new architecture of bearer network were proposed.